2014
DOI: 10.4028/www.scientific.net/amm.580-583.632
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics Analysis of Flexible Base Pavement Structure

Abstract: With the rapid development of traffic cause in our country, the operating requirement of driving load factors to pavement structure become higher and higher. The Semi-rigid base asphalt pavement structure exposed some defects and shortcomings, so the study of flexible base asphalt pavement structure is put on the agenda under the circumstances.Based on the research achievements at home and abroad of the existing asphalt pavement structure , choosing different elastic modulus and thickness to calculate and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…ANSYS was used to compute and analyze the foundation of a flexible base asphalt pavement system with various elastic moduli and thicknesses. As a result, a response regarding pavement structure for the base foundation was obtained, serving as a design reference [68]. Also, a comparison of the season-dependent equal temperature to the effect of seasonal temperature changes on the fatigue strength of flexible and semi-rigid pavement systems of flexible and semi-rigid pavement systems at the yearly equivalent temperature of 10℃was performed [69].…”
Section: Ansysmentioning
confidence: 99%
“…ANSYS was used to compute and analyze the foundation of a flexible base asphalt pavement system with various elastic moduli and thicknesses. As a result, a response regarding pavement structure for the base foundation was obtained, serving as a design reference [68]. Also, a comparison of the season-dependent equal temperature to the effect of seasonal temperature changes on the fatigue strength of flexible and semi-rigid pavement systems of flexible and semi-rigid pavement systems at the yearly equivalent temperature of 10℃was performed [69].…”
Section: Ansysmentioning
confidence: 99%
“…The latest National Highway Network Planning points out that China will build 26,000 kilometers of expressways and 34,000 kilometers of ordinary highways by 2035. However, there are common problems for the current road subgrade, such as poor coordination of rigid subgrade deformation, difficulty in controlling reflective cracks in semi-rigid subgrade, and low bearing capacity of flexible subgrade, which seriously affects the quality of road surface [1]. In addition, the rapid development of transportation has led to an increasing demand for materials such as cement and lime in road subgrade construction.…”
Section: Introductionmentioning
confidence: 99%
“…Qi [11] studied the dynamic and static spring back modulus tests and field CBR tests of continuously graded crushed stone base materials in the laboratory and found that with an increase in the load capacity, the modulus of graded crushed stone materials gradually increased. Li [12] compared the mechanical characteristics of semi-rigid pavement and flexible pavement and obtained the influence law of different structural layer thicknesses on pavement load and the mechanical response law and trend of asphalt pavement structural layer. Through a lot of research on the mechanical properties of base layer material, the load capacity of base layer material was constantly optimized and improved, which was conducive to reducing transverse shrinkage cracking of asphalt pavement [13,14].…”
Section: Introductionmentioning
confidence: 99%